Is Passive Smoking a Risk Factor for Postmenopausal Osteoporosis? - Original Investigation - Osman Altunbayrak; Merih Sarıdoğan; Güler Ateşer; Ülkü Akarırmak; Deniz Palamar (Galenos Yayinevi, 2009)
Aim: We aimed to show whether or not passive smoking is a risk factor for postmenopausal osteoporosis. Material and Methods: 250 postmenopausal women between the ages 40-65, who have not had menstruated for at least one year, had FSH>40mIU/ml, have not secondary osteoporosis cause and who naturally entered menopause were engaged in the study. Cases were divided into three study groups depending on their relations with cigarettes (Aİ: active smokers, Pİ: passive smokers, K: Control) and the groups are collated in terms of postmenopausal osteoporosis risk factors. BMD were measured with the DXA method. Results were evaluated as according to the measurements of WHO. ANOVA and Tukey HSD, Kruskal Wallis, Mann Whitney U and K-Square tests were applied for statistical analysis. p<0.05 value was accepted statistically meaningful. Results: Aİ consume more tea-coffee at a significant level when compared with Pİ and K (p<0.001). Pİ use more Ca and Vit-D supplementes and ARZ-OAB (antirezorptive-osteoanabolic) medicine at a significant level when compared with Aİ and K (p<0.05, p<0.01). There were no statistical differences between the groups in terms of education, consumption of milk and dairy products, consumption of salt, daily Ca amount taken on a diet, habit of postmenopausal exercising, fracture anamnesis, story of osteoporosis in the family, menarche age, menopause age and time, fertility time and use of HRT. K are more the values of BMD and T-Score belonging to L1-L4 Vertebral and Femur Neck at a significant level when compared with Pİ and Aİ (p<0.001). Discussion: Some features have found at a higher level in Pİ, which have positive effect on BMD (such as high BMI average, more Ca and Vit-D supplementes usage and more ARZ-OAB usage) and in Aİ, which have a negative effect on BMD (such as low BMI, urban life, more tea-coffee consumption). Nevertheless, the data we found indicated that there was going to be low bone density in the L1-L4 Vertebra and femur neck levels at a high level in Pİ as well as Aİ. Conclusion: It has been decided that passive smoking is a significant risk factor for postmenopausal osteoporosis. (From the World of Osteoporosis 2009;15:38-42)